Biology-enabling inositol phosphates, phosphatidylinositol phosphates and derivatives. - Conway, S; Miller, G (2007)
This review highlights inositol polyphosphate- and phosphatidylinositol-based small molecule probes that have advanced our understanding of intracellular signalling.